Oncogenic B-RAF(V600E) signaling induces the T-Box3 transcriptional repressor to repress E-cadherin and enhance melanoma cell invasion. - Boyd, S; Mijatov, B; Pupo, G; Tran, S; Gowrishankar, K; Shaw, H; Goding, C; Scolyer, R; Mann, G; Kefford, R; Rizos, H; Becker, T (2013)
Approximately 50% of melanomas require oncogenic B-RAF(V600E) signaling for proliferation, survival, and metastasis, and the use of highly selective B-RAF inhibitors has yielded remarkable, although short-term, clinical responses. Reactivation of signaling downstream of B-RAF is frequently associated with acquired resistance to B-RAF inhibitors, and the identification of B-RAF targets may therefore provide new strategies for managing melanoma. In this report, we applied whole-genome expression analyses to reveal that oncogenic B-RAF(V600E) regulates genes associated with epithelial-mesenchymal transition in normal cutaneous human melanocytes. Most prominent was the B-RAF-mediated transcriptional repression of E-cadherin, a keratinocyte-melanoma adhesion molecule whose loss is intimately associated with melanoma invasion and metastasis. Here we identify a link between oncogenic B-RAF, the transcriptional repressor Tbx3, and E-cadherin. We show that B-RAF(V600E) induces the expression of Tbx3, which potently represses E-cadherin expression in melanocytes and melanoma cells. Tbx3 expression is normally restricted to developmental embryonic tissues and promoting cell motility, but it is also aberrantly increased in various cancers and has been linked to tumor cell invasion and metastasis. We propose that this B-RAF/Tbx3/E-cadherin pathway has a critical role in promoting the metastasis of B-RAF-mutant melanomas.